Banks’ Cost Efficiency Determinants study: Evidences from the Germany and Greece - Liu, Wei (2013)
In recent years, banks played such important roles that some of them were too big to fail since whose failure may be disastrous to the whole economy. For instance, the financial crisis in 2008 might be a result of important financial institutions' failure, which led to catastrophe and unsteady to social economy. Thus, research on bank efficiency can be very meaningful in risk management study. This research will aim on estimating the cost efficiency of the financial industries in Germany and Greece. Final findings reveal that banks’ internal factors have made effect on cost efficiency. A stable and increasing trend could be found in the efficiency estimation result from 2006 to 1010 and witnessed a fluctuation which might be caused by the Europe debt crisis in 2009. Furthermore, the regression result provided information that scale economics, return on average equity and loan loss reserve could have a high correlation with the cost efficiency in both countries. However, there may be still many differences between these two countries (Germany and Greece) which need to be discussed in the upcoming article.